Risk factors for ST- Elevation Myocardial Infarction in a tertiary hospital in central Nepal - Dhungel, Sachin; Laudari, Shankar; Dubey, Laxman; Panjiyar, Rajesh; Upadhyay, Hari; Subramanyam, G (Journal of College of Medical Sciences-Nepal, 2017)
Background & Objectives: Coronary artery disease is the common cardiac disease in Nepal. The objective of the study is to explore different risk factors for coronary artery disease. Materials & Methods: This was cross sectional hospital based study studying the baseline clinical and angiographic characters in ST Myocardial infarction who had Primary Percutaneous coronary intervention (PPCI) in College of Medical Science Teaching Hospital (CMSTH). Results: There were 95 cases with male 77 (82.1%) and female 18 (17.9%). The mean age overall was 60.05 ± 12.2. The mean age of male was 59.9 ± 12.5 and of female was 60.5 ± 11.2 years. Apart from chest pain, common clinical symptoms were sweating in 60 (63.2%) cases, dyspnea in 41 (43.2%), nausea/vomiting in 38 (40%), dizziness in 17 (17.9%) and epigastric pain in nine (9.5%) cases. Common risk factors were smoking in 83 (87.7%) cases, hypertension 59 in (51.6 %), diabetes in 24 (25.3%), dyslipidemia in 24 (25.3%) and family history in six (6.3%) cases. Common angiographic variables were single vessel disease (SVD) in 45 (47.4%), double vessel disease (DVD) in 20 (21.1%) and triple vessel disease (TVD) in 30 (31.6%) cases. Infarct related artery were Right coronary artery (RCA) in 43 (45.3%), Left circumflex artery (LCx) in seven (7.4 %) and Left anterior descending artery (LAD) in 45 (47.4 %) cases. Conclusion: Patients visiting CMSTH had classical symptoms and risk factors of myocardial infarction. Single vessel disease and Left anterior descending infarction was the most common vessel involved.